Emerging Role of Syndecans in Extracellular Matrix Remodeling in Cancer. (December 2020) - Jang, Bohee; Kim, Ayoung; Hwang, Jisun; Song, Hyun-Kuk; Kim, Yunjeon; Oh, Eok-Soo
The extracellular matrix (ECM) offers a structural basis for regulating cell functions while also acting as a collection point for bioactive molecules and connective tissue cells. To perform pathological functions under a pathological condition, the involved cells need to regulate the ECM to support their altered functions. This is particularly common in the development of cancer. The ECM has been recognized as a key driver of cancer development and progression, and ECM remodeling occurs at all stages of cancer progression. Thus, cancer cells need to change the ECM to support relevant cell surface adhesion receptor–mediated cell functions. In this context, it is interesting to examine how cancer cells regulate ECM remodeling, which is critical to tumor malignancy and metastatic progression. Here, we review how the cell surface adhesion receptor, syndecan, regulates ECM remodeling as cancer progresses, and explore how this can help us better understand ECM remodeling under these pathological conditions